The one hundredth day of school! - Klein, Abby (Klein, Abby. Ready, Freddy!, 2008)
Freddy decides to bake one hundred cookies for the one hundredth day of school celebration, but his father accidentally eats one and then Freddy has to come up with another idea at the last minute.